A new hybrid routing protocol for wireless sensor networks. (2018) - Chelbi, Slaheddine; Dhahri, Habib; Abdouli, Majed; Duvallet, Claude; Bouaziz, Rafik
Wireless sensor networks (WSN) differ from traditional wireless communication networks in several characteristics. One of these characteristics is power awareness. In order to save the overall energy of the system and to fairly balance the load among nodes, we propose a new clustering routing protocol based on coverage control which incorporates two modules: (1) a scheduling mechanism based on binary particle swarm optimisation (PSO); (2) a cluster based protocol using fuzzy C-means (FCM) algorithm. Yet, in cluster based approach, the cluster head (CH) is usually selected amongst the sensor nodes which can die quickly for this extra workload. To mitigate this problem, we introduce some energy-harvesting (EH) nodes in the network which serve as CH. Since, the EH nodes are more expensive than the sensors, we study, in this paper, how to efficiently deploy EH nodes. Simulation results show that our protocol achieves an obvious improvement on the network lifetime.